One pot two-step borylation/fluorination reaction of dysobinin from Chisocheton macrophyllus and its cytotoxicity against cancer cell - Huda, Muhammad Badrul; Nurlelasari; Safriansyah, Wahyu; Fajar, Mohamad; Widiyowati, Iis Intan; Supratman, Unang; Permana, Yessi; Budiman, Yudha P. (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Dysobinin is a naturally occurred limonoid, which is a specific form of triterpenoid, mostly found in certain plants, particularly the Meliaceae family. Overall, it has been found that limonoids have a wide range of biological functions. Typically, the compound comprises anticancer, antimicrobial, and anti-inflammatory properties. Even though dysobinin has shown some effectiveness, its potential in pharmacology, so far, is found limited. This study, therefore, aims to enhance the pharmacological properties of dysobinin through the addition of fluorine. To do this, a one-pot, two-step reaction comprising C-H borylation and selectfluor was used to turn dysobinin into two new compounds: 1,2-dihydro-6?-acetoxyazadirone (5) and 1?-fluorodysobinin (6). After the transformation, various spectroscopic methods, including UV (Ultraviolet), IR (infrared), MS (mass spectra), as well as NMR (1D and 2D) were applied to figure out the structures of the new compounds. Accordingly, of the derived compounds, 1?-fluorodysobinin showed significantly higher cytotoxicity against A549 lung cancer cells when compared to dysobinin.